Inovasi Digital: Pemicu Intensi Wirausaha Mahasiswa Universitas Jambi - Heriyani, Heriyani; Sahara, Sahara; Dahlia, Dahlia (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2024)
This study aims to analyze the effect of creativity, digital literacy, and self-efficacy on the entrepreneurial intentions of Jambi University students. With a quantitative approach using the survey method, this study involved 100 respondents taken from the active student population using a purposive sampling technique. Hypothesis testing using SPSS 25 with multiple linear regression analysis tools. The results showed that creativity, digital literacy, and self-efficacy partially had a significant effect on the entrepreneurial intentions of Jambi University students. In contrast, the results of simultaneous testing showed that creativity, digital literacy, and self-efficacy had a significant effect on student intentions. The R2 test results show that creativity, digital literacy, and self-efficacy affect entrepreneurial intentions by 88.60%, while other variables explain the remaining 11.40%.